Virulence and resistance patterns of Vibrio cholerae non-O1/non-O139 acquired in Germany and other European countries - Schmidt, Katarzyna; Scholz, Holger C.; Appelt, Sandra; Michel, Jana; Jacob, Daniela; Dupke, Susann (Frontiers in Microbiology, 2023)
Global warming has caused an increase in the emergence of Vibrio species in marine and estuarine environments as well as fresh water bodies. Over the past decades, antimicrobial resistance (AMR) has evolved among Vibrio species towards various antibiotics commonly used for the treatment of Vibrio infections. In this study, we assessed virulence and resistance patterns of Vibrio cholerae non-O1/non-O139 strains derived from Germany and other European countries. A total of 63 clinical and 24 environmental Vibrio cholerae non-O1/non-O139 strains, collected between 2011 and 2021, were analyzed. In silico antibiotic resistances were compared with resistance phenotypes according to EUCAST breakpoints. Additionally, genetic relatedness between isolates was assessed by two cgMLST schemes (SeqSphere+, pubMLST). Both cgMLST schemes yielded similar results, indicating high genetic diversity among V. cholerae non-O1/non-O139 isolates. Some isolates were found to be genetically closely related (allelic distance <20), which suggests an epidemiological link. Thirty-seven virulence genes (VGs) were identified among 87 V. cholerae non-O1/non-O139 isolates, which resulted in 38 virulence profiles (VPs). VPs were similar between clinical and environmental isolates, with the exception of one clinical isolate that displayed a higher abundance of VGs. Also, a cluster of 11 environmental isolates was identified to have the lowest number of VGs. Among all strains, the predominant virulence factors were quorum sensing protein (luxS), repeats-in-toxins (rtxC/rtxD), hemolysin (hlyA) and different type VI secretion systems (T6SS) genes. The genotypic profiles revealed antibiotic resistance genes (ARGs) associated with resistance to beta-lactams, quinolones, macrolides, tetracycline, antifolate, aminoglycosides, fosfomycin, phenicols and sulfonamide. Carbapenemase gene VCC-1 was detected in 10 meropenem-resistant V. cholerae non-O1/non-O139 isolates derived from surface water in Germany. The proportion of resistance among V. cholerae non-O1/non-O139 species isolates against first line treatment (3 rd generation cephalosporin, tetracycline This is a provisional file, not the final typeset article and fluoroquinolone) was low. Empirical treatment would likely have been effective for all of the clinical V. cholerae non-O1/non-O139 isolates examined. Nevertheless, carbapenem-resistant isolates have been present in fresh water in Germany and might represent a reservoir for ARGs. Monitoring antimicrobial resistance is crucial for public health authorities to minimize the risks for the human population.